The Cultural Narrative as a Digital Promotion Strategy in Selling Batik Tulis Lasem and Its Effect on The Economy in Lasem - Tessa Eka Darmayanti; Ariesa Pandawangi; Dewi Isma Aryani; Belinda Sukapura Dewi; Ismet Zainal Effendi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
In 2022, the pandemic Covid-19 has entered its second year and has severely hit the national and regional economic sectors. One of them is the sale of batik Tulis in Lasem. However, the situation triggers cultural awareness of the local community to raise stories about batik as a sales strategy. So that the buyers are not only buying because of the beauty of the pattern but also know the cultural meaning within it. This study aims to look at and analyse the intangible cultural narrative could be a good promotion in selling batik Tulis Lasem through digital platform in the pandemic era and the impact to the Lasem’s economic condition. This qualitative research uses phenomenology approach and collecting detailed data from various sources related to the object of this study. The results show that the strategy provides economic improvement during the pandemic and ignites other creative ideas in digital sales. The research proves that “limited” circumstances do not rule out the possibility to contribute to the improvement of the regional economy while maintaining the sustainability of local culture.